We stand on guard for thee: A brief history of pest surveillance on the Canadian Prairies. (November 2021) - McCallum, Brent D.; Geddes, Charles M.; Chatterton, Syama; Peng, Gary; Carisse, Odile; Turkington, T. Kelly; Olfert, Owen; Leeson, Julia; Sharpe, Shaun; Stephens, Emma; Hervet, Vincent; Aboukhaddour, Reem; et al.
Abstract: Crop production had dominated the Canadian Prairies for the past century, and has been constantly challenged by various pathogens, insects, and weeds. An effective biovigilance program to manage these crop pests requires continuous, timely, and detailed pest surveillance, to understand how pest populations are changing over time. Many of these pests have been managed through surveillance and various mitigation strategies, combined with follow-up analyses. Pest surveillance activities have been documented in the Canadian Prairies for over 100 years and analysis has progressed from determining the pest species involved, to understanding the damage they cause, their biology, spread, over-wintering strategies, reproduction, pesticide resistance, and genetic diversity. This research has generated a continuous history of the pest populations for crops in western Canada. Detailed virulence analysis has revealed pathogen evolution and adaptation to overcome some of the deployed host resistance genes. Some weed, insect, and plant pathogenic fungal species have evolved to become resistant to pesticides. Integration of pest surveillance activities will help to build a more responsive, robust, and reliable biovigilance program to manage crop pests in the Canadian Prairies. Highlights: Historic review of pest surveillance in the Canadian Prairies. Evolution, spread, and damage caused by the major pathogens, weeds and insects affecting crops in western Canada. Thorough, detailed and continuous pest surveillance is essential to effective biovigilance in crops. Detection of the appearance of pesticide resistance in pathogens, weeds and insects.